Small business exposed: The tribes that drive economies - Holmes, S.; Schaper, Michael (2018)
© 2018 Scott Holmes and Michael T. Schaper. This book is a look into the world of the small business owner through their eyes how the five different “tribes” of business perceive the world around them, how they run their businesses, their motivations and goals. Its not another “how to” book or an academic treatise. Everyones needs and hopes are different; however, by using cutting-edge social scientific research techniques, we break the business community into five groups (or tribes): The Seekers, Whatnows, Drifters, Satisficers and Digitals. Each tribe has its own set of issues. And there are also some things which cut across all the tribes the consistent elements in small business owners DNA. Understanding which tribe you belong to could make the difference in growing your business or help you better advise businesses to achieve their goals. Small Business Exposed will bridge the gap between the frontiers of small business research and the popular business book market. As such, it will become an essential text not only for the small businessperson, but also enter the libraries of advisors, accountants, bankers and anyone else with a vested interest in the business economy.